Analysis of Verbs in the Asilulu Language - Tutupara, Velia Rosalinda; Sasabone, Carolina; Parinussa, Jolanda Dessye (Universitas Pattimura, 2024)
The use of audio-visual learning media is used to see the influence of learning outcomes of grade VII students of SMP Negeri 7 Ambon in writing descripty texts. This research was conducted by quantitative research method descripty. The research process is obtained through data collection techniques which include observation, interviews, learning processes, questionnaires and documentation. Observation is used by researchers to observe the learning process carried out by subject teachers and grade VII students. Interview is a process of taking data from teachers to determine the level of student understanding. The learning process is an advanced stage carried out by researchers to use audio-visual learning media in writing description text materials. Questionnaire is one of the tools used to find out students' interest in learning the material of writing description texts using audio-visual learning media. Docuumentation is the process of taking photos to be used as research data. The analysis of the data obtained in this study is the influence of learning outcomes obtained from grade VII students in learning the material for writing description texts. This is what makes this study has provided answers for the use of audio-visual learning media for the learning outcomes of grade VII students of SMP Negeri 7 Ambon.